Analysis of Court Decision on The Burden of Proof as A Legal Requirement for Divorce, based on The Civil Code and The Compilation of Islamic Law - Andi Dedi Wijaya; Indah Kusuma Wardhani (Asian Journal of Social and Humanities, 2026)
Marital life between husband and wife does not always go smoothly; couples experience numerous obstacles that drive them to opt for divorce. This situation also affects Catholic couples, many of whom choose to file for divorce through state courts even though the Catholic Church forbids and does not recognize divorce. The normative juridical research method with a case study approach utilizing primary, secondary, and tertiary legal materials is the research methodology employed. The application of the burden of proof in divorce proceedings, as well as the perspectives of positive law and the Catholic Church regarding the legitimate requirements for divorce, are the research issues investigated. The findings demonstrate that the judge's reasoning in the ruling — which states that the plaintiff must prove the grounds for divorce as outlined in Article 163 HIR — is satisfied by written evidence and two witnesses who attest that the Catholic couple seeking a divorce has, in fact, not lived together for an extended period. Positive law views divorce as a right of married couples, in contrast to Catholicism, which regards marriage as sacred and indissoluble and holds that a Catholic marriage can only be dissolved by death. In other words, if one of the Catholic parties remarries after the state court has dissolved the first marriage, the Catholic Church still considers the prior marriage to be valid and the new marriage to be invalid, classifying it as adultery.